Strang Split-Step FDTD Formulations for Modeling Dispersive Electromagnetic Applications - Ramadan, Omar (IEEE-Inst Electrical Electronics Engineers Inc, 2010)
Unconditionally stable split-step finite-difference time-domain (SS-FDTD) formulations are presented for modeling dispersive electromagnetic applications. The formulations are based on incorporating the Strang split-step approach into the complex envelope FDTD (CE-FDTD) algorithm. A numerical example carried out in two-dimensional (2D) domain shows that the proposed formulations provide better accuracy than the CE locally one-dimensional SS-FDTD (CE-LOD-FDTD) counterpart with a considerable reduction in the CPU time requirement.
Keywords: Complex envelope finite-difference time domain (CE-FDTD); dispersive media; Strang split-step